Ljudje v turizmu: Izbrana poglavja iz managementa človeških virov v turizmu - Gorenak, Mitja (University of Maribor Press, 2020)
People in Tourism: Selected Chapters from Human Resources Management in Tourism. Human Resource Management is a complex mix of activities that managers must perform in order to optimize the performance of the entire organization. In the case of an organization in the service sector, which includes tourism, matters are even more complicated, as success depends on the direct satisfaction of the customer. The book intertwines chapters related to the field of management, as well as more sociologically and psychologically colored topics. Thus, we begin the book with a chapter on the values ​​of the individual, from which the values ​​of the organization later follow. Both topics are inextricably linked to the rest, as they represent the foundation of the work of the individual and any organization. The chapters on organizational culture and social responsibility follow, which demonstrates the so-called "modus operandi" of the organization. The following are the chapters on competencies, management, and performance appraisal, which talk about the relationship between the individual and the organization. The book is concluded with three chapters, mainly related to the current operational requirements in the organization, namely the chapters on commitment, motivation, and intergenerational management in the organization.